Bird and rodent pest control in select California crops: economic contributions, impacts, and benefits - Schein Dobb, Jennifer, author; Loomis, John, advisor; Kling, Robert, committee member; Shwiff, Stephanie, committee member; Anderson, Aaron, committee member (Colorado State University. Libraries, 2014)
Although numerous factors affect agriculture production, significant yield and quality losses of crops have been attributed to wildlife, insects, and diseases; collectively known as pests. To mitigate pest activity agricultural producers utilize a variety of control tools and techniques including rodenticides, trapping, exclusion, and chemical aversion (Sexton et al., 2007); causing integrated pest management to become an integral part of modern agricultural production. Although crop savings is arguably the most important contribution of pest control, relatively few studies have attempted to quantify prevented crop loss and the economic impacts of these cost savings. This study found that current California control practices as applied to alfalfa, almonds, avocados, carrots, cherries, citrus, grapes, lettuce, melons, peaches, pistachios, rice, strawberries, tomatoes, and walnuts were effective at mitigating crop loss which had the potential to significantly restrict the domestic supply of these agricultural commodities. These practices were shown to lower wholesale prices and were estimated to prevent multi-million dollar losses to California growers, and multi-billion dollar losses to consumers nationwide. In addition to the direct benefits realized through these crop savings, the production and sale of these additional yields further stimulates economic activity within the state. Modeling the forward and backward linkages between California suppliers and consumers enabled monetary flows in secondary markets to be quantified, providing a more conclusive estimate of the total benefits of bird and rodent control in California. This study found that expenditures related to the production of additional yields protected from rodent damage contributed $1.7 billion to California's economy and supported 23,000 jobs, with farm revenue earned on these yields supporting another 11,000 California jobs and contributing nearly $951 million to the state's economy. Findings from this study also estimated that the production of yields protected from bird damage were estimated to contribute $1.39 billion to the state's economy and supported more than 20,000 jobs, with farm revenue earned on these yields supporting another 6,775 jobs and contributing another $565 million to California's economy.